The Effect of Oxytocin Massage on Breast Milk Production in Ciledug Health Center Cirebon Regency - Minarni, Ani; Mutya Sari, Vianty; Aliah, Nur; Rizki Nurfita, Nisa (Ann Publisher, 2023)
Stunting is an increasingly common problem in developing countries, including Indonesia. In Cirebon Regency, especially in Ciledug District, stunting cases amounted to 13.6% in 2018. The magnitude of the benefits of breastfeeding is not offset by an increase in breastfeeding behavior. According to WHO, more than 40% of babies are introduced too early to complementary foods. One way to increase production is oxytocin massage. Oxytocin massage is performed to stimulate the oxitocin reflex or letdown reflex. The increase in the number of breastfeeding mothers globally has the potential to save the lives of more than 820,000 children under five years old and could prevent an additional 20,000 cases of breast cancer in women each year. This study used the pre-experiment method using one group pretest-post test design, a design experiment that uses one group of subjects and takes measurements before and after giving treatment to subjects. The milk production of postpartum mothers before oxytocin massage has an average of 23.10 ml, while after oxytocin massage the milk production of postpartum mothers has an average of 61.43 ml. The paired sample T test results were obtained significantly by 0.000 (p-value < 0.05). The results of the study found that there was an effect of oxytocin massage on breast milk production. There is a difference in milk production before and after oxytocin massage. It is expected to be able to apply the implementation of oxytocin massage to postpartum mothers in health services.